1990
DOI: 10.1111/j.1365-2982.1990.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase Activity of Histamine H2‐Receptor Antagonists in the Dog: Their Possible Role in Gastric Motor Activity

Abstract: We studied the anticholinesterase activity of three H2‐receptor antagonists (cimetidine, ranitidine, and famotidine) in vitro and in conscious dogs with chronically implanted strain‐gauge force transducers. In vivo, acetylcholine (ACh) was infused intravenously at a dose of 0.05 mg/(kg · min) for 5 minutes with or without a background continuous intravenous infusion of H2‐receptor antagonists or neostigmine during the quiescent period of the interdigestive state. Cimetidine and ranitidine enhanced the ACh‐indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…the circular system, gland secretion, intestinal transit, and defecation as adverse events. It has been reported that neostigmine, cimetidine, and ranitidine decrease blood pressure in experimental animals [21,23]. Both in non-clinical and clinical studies on nizatidine, no severe AChE inhibition-related adverse events including a fall in blood pressure and severe diarrhea have been observed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…the circular system, gland secretion, intestinal transit, and defecation as adverse events. It has been reported that neostigmine, cimetidine, and ranitidine decrease blood pressure in experimental animals [21,23]. Both in non-clinical and clinical studies on nizatidine, no severe AChE inhibition-related adverse events including a fall in blood pressure and severe diarrhea have been observed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence currently available on the use of ranitidine as a prokinetic agent pertains, for the vast majority, to experimental settings. Five single centred experimental non-randomised non-blinded crossover studies (Fioramonti et al, 1984;Bertaccini et al, 1985;Mizumoto et al, 1990;Kishibayashi et al, 1994;and Lidbury et al, 2012) investigated potential prokinetic properties of ranitidine both in vitro (Bertaccini et al, 1985;and Mizumoto et al, 1990) and/or in vivo on healthy conscious or anaesthetised dogs (Fioramonti et al, 1984;Bertaccini et al, 1985;Mizumoto et al, 1990;Kishibayashi et al, 1994;and Lidbury et al, 2012). Although four out of five studies (Fioramonti et al, 1984;Bertaccini et al, 1985;Mizumoto et al, 1990; and Kishibayashi et al, 1994) found some degree of gastrointestinal motility stimulation post-ranitidine administration, these results are difficult to compare and generalise due to the limited number of animals included in each study, different patient populations evaluated (conscious vs anaesthetised, starved vs non-starved), a variety of techniques employed to estimate GI motility and discordant dosing regimes or route of administration.…”
Section: The Evidencementioning
confidence: 99%
“…The few studies centred on its role as an acetylcholinesterase inhibitor and prokinetic have mainly been carried out in experimental settings and on healthy canine patients (Fioramonti et al, 1984;Bertaccini et al, 1985;Mizumoto et al, 1990;Kishibayashi et al, 1994;and Lidbury et al, 2012). Two studies included in vitro experiments (Bertaccini et al, 1995;and Mizumoto et al, 1990) and they both proved ranitidine to have consistent anticholinesterase properties. The same papers also showed a pro-kinetic effect in vivo at clinically relevant doses.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%